The Impact of Risk Management & Internal Audit on Credit Provision Policy at PT Bank Sumut Lotu Branch - Farrel Arvid Faoloaro Zai; Duma Megaria Elisabeth; Farida Sagala (Jurnal Ilmiah Accusi, 2025)
This study aims to analyze the effect of risk management and internal audit implementation on credit policy at PT Bank Sumut Lotu Sub-Branch. The background of this research is the significant difference between credit disbursed and credit repaid, as well as the suboptimal implementation of risk management and internal audit in credit policy. This study uses an explanatory method with a quantitative approach. The research population consists of all employees in the credit division of PT Bank Sumut Lotu Sub-Branch, totaling 17 people, with saturated sampling technique so that the entire population is used as the sample. Data were collected through questionnaires using a Likert scale and analyzed using SPSS with multiple regression analysis technique. The results show that risk management has a negative and significant effect on credit policy (ttabel = 2,145; t = -6.132; p = 0.000), indicating that the stricter the implementation of risk management, the more conservative the credit policy becomes. Internal audit has a positive and significant effect on credit policy (β = 1.577; t = 8.416; p = 0.000), showing that effective internal audit improves the quality of credit policy. Simultaneously, both variables have a significant effect on credit policy with an F-calculated value of 36.463 (p = 0.000) and a coefficient of determination (R²) of 83.9%, indicating that both variables can explain 83.9% of the variation in credit policy. This study concludes that risk management and internal audit are two complementary functions in supporting the establishment of effective credit policies in banking